Analisis Layanan Pemberdayaan yang Dilakukan oleh Lembaga Amil Zakat Nasional Yatim Mandiri pada Anak Yatim di Surabaya - Santoso; Ubaid Aisyulhana (AL-UJRAH, 2024)
The background of this research are: First, there are many amil zakat institutions in Indonesia that have not been able to collect zakat, infaq, and sadaqah funds optimally. Second, there is still public distrust of institutions in channeling zakat, infaq, and sadaqah funds, so that people still rely on the old way, namely direct distribution. Third, the service of zakat institutions in serving mustahik should be improved because it is related to satisfaction and family ties between parties who have mustahik amil zakat institutions. The results of this study are as follows: First, the empowerment carried out by Yatim Mandiri includes various things and aspects of life, such as the economy, education, health services, humanity, da'wah and others. Second, each of these aspects has a special program such as community empowerment to youth. Third, Yatim Mandiri as a national amil zakat institution that focuses on building the independence of orphans / poor people also conducts empowerment programs for the poor. The services provided by Yatim Mandiri to the poor and needy benefit very well and pay attention to the conditions of the mustahik. Overall, the conclusion of this study is that Yatim Mandiri has carried out its duties optimally as evidenced by the very positive assessment of mustahik and the empowerment of the poor.